2009
DOI: 10.4103/0250-474x.58175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcoholic extracts of Indian medicinal plants on the altered enzymatic activities of diabetic rats

Abstract: In present study, the effect of alcoholic extract of Momordica charantia, Aegle marmelos and Eugenia jambolana was studied on serum glutamic oxaloacetate transminase and serum glutamic pyruvate transminase activities and on serum urea, total protein and albumin concentrations of streptozotocin diabetic rats. Diabetes in rats was induced by single dose of streptozotocin (30 mg/kg i. p.). On confirming the diabetes after 48 h of injection, alcoholic extracts of three plants were administered orally in doses of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
5
12
1
Order By: Relevance
“…The results are in contrast to Rajasekaran et al (2009) and Sundaram et al (2009) who found significant (P<0.05) reduction in SGOT activity due to administration of A. marmelos. In accordance with results of present experiment on Chelidonium supplementation Vakil et al (1989) and Rawling et al (2009) , while Gawronska et al (2009) and Banerjee et al (2010 observed decrease in the activity of SGPT.…”
Section: Serum Glutamate Pyruvate Transaminase (Sgpt)contrasting
confidence: 98%
See 3 more Smart Citations
“…The results are in contrast to Rajasekaran et al (2009) and Sundaram et al (2009) who found significant (P<0.05) reduction in SGOT activity due to administration of A. marmelos. In accordance with results of present experiment on Chelidonium supplementation Vakil et al (1989) and Rawling et al (2009) , while Gawronska et al (2009) and Banerjee et al (2010 observed decrease in the activity of SGPT.…”
Section: Serum Glutamate Pyruvate Transaminase (Sgpt)contrasting
confidence: 98%
“…The maximum values were recorded in treatment group T3 (5.51 g/dl) while minimum in guinea fowls of group T1 (4.50 g/dl). Similar to the result of present study Immanuel et al, (2009) Meshram et al andSundaram et al (2009) Globulin: Maximum value of serum globulin (Table 1) was noted in the treatment group T3 (3.19 g/dl) while minimum value in T1 group (2.51 g/dl). As regards A. marmelos and B. diffusa, Ongmoo (2011) found a non-significant impact of both mother tinctures on serum globulin levels in layers, however results of Chelidonium mother tincture supplementation are similar with those of Vakil et al (1989).…”
Section: Total Serum Proteinsupporting
confidence: 91%
See 2 more Smart Citations
“…Many studies in the past two decades have shown that the seed (Achrekar et al 1991;Panda et al, 2009;Rathi et al 2002;Ravi et al, 2005Ravi et al, , 2004aRavi et al, , 2004bRavi et al, , 2004cRavi et al, , 2004dSharma, Balomajumder and Roy, 2008b;Sharma, Balomajumder and Roy, 2008b;Sharma, Viswanath, et al, 2008a;Sharma, Viswanath, et al, 2008a;Sharma et al 2003;Sridhar et al 2005), the fruit pulp (Achrekar et al, 1991;Pepato et al, 2005;Sharma et al, 2006;Sundaram et al, 2009) and bark (Villasenor and Lamadrid, 2006) possess antihyperglycemic effects, while the leaf was ineffective and devoid of this pharmacological effects (Pepato et al, 2001). The seed has been subjected to detailed investigations and observations suggest that it is effective when given as powder (Sridhar et al, 2005) or as an extract (Achrekar et al, 1991;Panda et al, 2009;Ravi et al, 2005Ravi et al, , 2004aRavi et al, , 2004bRavi et al, , 2004cRavi et al, , 2004dSharma, Balomajumder and Roy, 2008;Sharma, Viswanath, et al, 2008;Sharma et al, 2003;Sundaram et al, 2009) in reducing both hyperglycemia and diabetic complications in the experimental animals.…”
Section: Antidiabetic Activitiesmentioning
confidence: 96%